Using a makerspace approach to engage Indonesian primary students with STEM - Blackley, Susan; Rahmawati, Y.; Fitriani, E.; Sheffield, Rachel; Koul, R. (Western Australian Institute for Educational Research Inc, 2018)
© 2018, Western Australian Institute for Educational Research Inc. All rights reserved. This paper examines the learning experiences of 291 Year 5 and 6 Indonesian primary school students, across four schools in North Jakarta, who participated in an integrated STEM project that used a 3-phase Makerspace approach: exposure, engagement and experimentation, and evaluation and extension. The Wiggle Bots project involved these students employing their skills and knowledge of technology and science to create a ‘bot’, and then completing a survey that examined their confidence, engagement, identification and application of science knowledge. The results indicated that a Makerspace approach was very effective in engaging students in the STEM space, and students were also challenged to work collaboratively in groups mentored by pre-service teachers. With the application of STEM knowledge and skills, we also posit that the Makerspace approach is effective in the acquisition and demonstration of 21st century skills: problem-solving, critical and creative thinking, collaboration, and communication.